Local Food Diversification Development Strategy in West Sumbawa Regency - Eko Supriastuti; Anton Anton; Ari Apriani; Fikri Rirahman (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
A method of food selection known as